Assessment of caries diagnostic threshold of DMFT, and ICDAS II in the estimation of caries prevalence rate in first permanent molars among students of College of Dentistry-Hawler Medical University. - Razawa Kareem Saeed; Mustafa Isa Omer; Neenor Nazar Hanna; Hallo Khals Ghafour (Erbil Dental Journal, 2024)
Background: Dental caries is a common chronic infectious disease resulting from tooth-adherent cariogenic bacteria primarily S. Mutans, which metabolize sugars to produce acid, demineralizing the tooth structure over time.